The challenges faced by school-based role-players in the implementation of SIAS: A comparative study - Iturralde, Inge (University of the Witwatersrand, Johannesburg, 2024)
The policy on Screening, Identification, Assessment and Support (SIAS) (DoE, 2014) is an inclusive policy enacted at school level which is designed to support inclusive education imperatives of Education White Paper 6 (DoE, 2001). The effective implementation of SIAS correlates with successful provisioning for learner support to enable access to quality education for all. However, it appears that there are multiple challenges experienced by school-based role-players to the implementation of the SIAS policy in schools, hindering it from achieving intended outcomes. Although limited research on challenges to SIAS implementation is available, a disjunct between policy and policy implementation is evident in literature regarding other inclusive education policy implementation in South Africa, setting the expectation that the SIAS policy is no different. This qualitative research study used a comparative case study design to determine the challenges to SIAS policy implementation experienced by school-based role- players at one mainstream school and one Learners with Special Educational Needs (LSEN) school in Gauteng. Participant perceptions, collected through the use of focus group interviews and open-ended questionnaires, were analysed using thematic content analysis in order to understand common challenges, as well as to identify challenges that were unique within each school context. The theoretical framework used the medical model of disability and the social model of disability as a lens through which to view the SIAS policy. The study findings demonstrate a complex interplay between the social and medical models of disability in how they inform teachers perceptions- and subsequent implementation- of the SIAS policy as a challenge to its enactment. Additionally, findings highlighted challenges with teacher perspectives and understandings of inclusion and the purpose of the SIAS policy, training and support of teachers and School Based Support Teams (SBSTs), communication and support amongst stakeholders, relationships and collaboration amongst stakeholders, form completion and documentation, variations in implementation procedures, class sizes and human resources, and policy incongruence with other policies. iv At present, there is a gap in available literature on the implementation of the SIAS policy as current literature tends to focus on the challenges experienced by District Based Support Teams (DBSTs). This study positions itself to address this gap by focussing on challenges faced by SBSTs and teachers themselves. Furthermore, this study expands on understandings of challenges to inclusive policy implementation. In doing so, the recommendations made intend to improve aspects of SIAS policy implementation in order to better support inclusive education imperatives and to secure more efficient and effective support for learners at the school level to ensure quality and equitable education is an accessible reality.
A research report submitted in fulfillment of the requirements for the Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; school-based role-players; SIAS; Policy implementation; school-based support team; SDG-4: Quality education